THE RELATIONSHIP BETWEEN EXERCISE PARTICIPATION AND THE OCCURRENCE OF OSTEOARTHRITIS: A SYSTEMATIC REVIEW - cinta, adel restasia (Universitas Teuku Umar, 2024)
AbstractBackground: Osteoarthritis (OA) is one of the most common joint diseases worldwide, affecting millions of adults across various age groups. There are several factors that cause cases Osteoarthritis one of them is a factor related to sports participation. The purpose this research is to determine the relationship between sports participation and cases Osteoarthritis. Method: The research method uses a system Systematic review with the PICO method (Population/Patient/Problem, Intervention, Comparison, Outcome). Article searches use 2 databases, namely Google Scholar and Pubmed and determine inclusion and exclusion criteria to determine which articles will be selected and reviewed. Results: Results based on 5 articles that have been reviewed show the results that there is a relationship between sports participation and cases of Osteoarthritis. The highest prevalence is Osteoarthritis cases in the knee in athletes and retired athletes. There are several factors for the occurrence of OA cases, namely age, body mass index (BMI), previous injury, and occupation. Conclusion: The conclusion from the review of the 5 articles can be concluded that there is a relationship between sports participation and cases of Osteoarthritis. Injury is one of the highest risk factors for OA cases. Repetitive injuries are also associated with a greater likelihood of OA.Keyword : Sports Players, Athletes, Osteoarthritis, Health